Effect of eye rubbing on corneal biomechanical properties in myopia and emmetropia - Li, Xia; Wei, Anji; Yang, Yujing; Hong, Jiaxu; Xu, Jianjiang (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: To investigate short-term changes in corneal biomechanical properties caused by eye rubbing in myopia and emmetropia and compare the differences between two groups. . Methods: This was a prospective observational study of 57 eyes of 57 healthy subjects aged 45 years and younger. All the subjects underwent eye rubbing by the same investigator using the same technique and with the same force. Biomechanical parameters were recorded using a Corvis ST device before and, after 1-minute eye rubbing One week later, all the participants underwent the test again. Statistical methods were employed to analyze the changes and determine independent factors affecting the stiffness parameter at the first applanation (SP-A1). Results: After 1-min of eye rubbing, the cornea was less stiff, as shown by the SP- A1 (P < 0.001). Higher deformation and deflection amplitudes (P < 0.001, P = 0.012), higher peak distances (P < 0.001), earlier A1 times (P < 0.001) and faster velocities (P < 0.001), and lower maximum inverse radii (P = 0.004) were observed. According to an automatic linear modeling analysis, there were two factors influencing the decrease of SP-A1: refractive states (B=-5.236, P=0.010) and bIOP (B=0.196, P= 0.016). Central corneal thickness (CCT) decreased only in the myopic group after eye rubbing (P = 0.039). The change in amplitude was larger in the myopic group than in the emmetropic group (P < 0.001). All the parameters returned to baseline level one week later. Conclusions: Eye rubbing appears to alter corneal biomechanical properties temporarily and make the cornea softer, especially for myopic young patients.